Effect of microbubble diameter, alkaline concentration and temperature on reactive oxygen species concentration. Issue 7 (9th January 2017) - Yu, Xiaobin; Wang, Zhonghang; Lv, Yeqing; Wang, Shaona; Zheng, Shili; Du, Hao; Zhang, Yi
ABSTRACT: BACKGROUND: In comparison with ordinary bubbles, microbubbles exhibit low floating rate and high surface charge density. More importantly, microbubbles shrink gradually and the gas–liquid interface charges congest significantly, generating large surface potential and energy, which promotes the formation of reactive oxygen species (ROS) when microbubbles eventually collapse. In this study, size‐controllable microbubbles were introduced to alkaline solutions by titanium microporous filters, and the effects of microbubble diameter, alkaline concentration and temperature on the formation of ROS were examined. RESULTS: Maximum ROS concentration was obtained by using a microporous filter with average pore size of 25 µm and 40 µm in NaOH and KOH solutions, respectively. Further, with increase in alkaline concentration and temperature, the formation of ROS both exhibited parabolic trends, and optimal temperature for ROS formation was determined to be 65 °C. The maximum ROS concentration was 1.05 mmol L −1 and 3.51 mmol L −1 in NaOH and KOH solutions, respectively, after aerating for 60 min. CONCLUSION: The formation of ROS is dependent on the bubble size and solution composition and is influenced by both temperature and alkaline concentration. The results further extend the range of ROS application and provide references for ROS regulations in alkaline media. © 2016 Society of Chemical Industry